Navigating straits : challenges for international law - Caron, David D.; Oral, Nilufer (Brill Nijhoff, 2014)
In Navigating Straits: Challenges for International Law, internationally recognized international law scholars provide in-depth analysis of the legal challenges in straits concerning security, piracy, safety and environmental protection. All readers interested in international and law of the sea will find this seminal volume of interest.